A Generic and Scalable Dynamic Model for Stationary Battery Energie Storage Systems - Richter, Julian; Sladek, Marc; Luther, Matthias (27th International Conference on Electricity Distribution, 2023)
Stationary second life battery energy storage systems (BESS) are becoming more relevant for distribution grids due to the increasing share of renewable energies. In contrast to first cycle BESS, uniform cell behavior within the BESS can no longer be assumed for second life BESS. This paper proposes a model of a stationary BESS, which can represent different battery technologies, down to the cell level. An active n-to-n balancing algorithm based on capacitors is implemented. In addition, the model is modular on stack and module level and equipped with automation for easy scalability. The results show that the balancing algorithm is suitable for second life BESS while simple scalability and realistic cell behavior can be realized.<br
CRIS-Team Scopus Importer:2024-12-16